Aging and health conditions: a prospective analysis of the socioeconomic impact of disability in the Portuguese population - Nogueira, D.; Reis, E. (Aging and Society: An interdisciplinary Journal, 2012)
In Portugal, the aging population phenomena has brought up socioeconomic concerns such as the need for more resources for providing health care and social support for dependent elderly. The objective of this research is to characterize the disability profile of the Portuguese elderly, and to make a prospective analysis of the impact of long term care on public expenditures. Data was obtained from the National Health Surveys carried out between 1987 and 2005. Descriptive analysis shows a predominance of females, low levels of literacy, self-perceived health status concentrated on “reasonable” and “bad”, and a higher prevalence of severe disabilities such as being confined to bed and dependent on feeding. A regression model applied to the 2005 health survey data reveals that age, sex, education, income, some chronic illnesses, and self-perception of health status are the variables that best explain the final disability score. Profiles emerging from further analysis support the development of prospective scenarios to project the economic impact of the use of long term care on public expenditures for the period 2010 to 2060. According to the population projections until 2060, public expenditure with formal care could increase 76% if health conditions remain similar to those of the 2005 health survey. If a scenario of expansion of morbidity is to be observed, public expenditure could increase 198%. In a scenario of compression of morbidity, public expenditure may decline 43%, and if levels of disability were in line with the last survey but with less severity, public expenditure could grow 32%. Future generations will most likely have different characteristics from those observed in the 2005 health survey in terms of some variables that explain dependency. Scenarios where longevity goes along with better health seem to be more probable, allowing a better control of public spending.